INCLUSIVE PHYSICAL EDUCATION AS A TOOL FOR FORMING THE EDUCATIONAL ENVIRONMENT FOR STUDENTS WITH DISABILITIES - Blavt, Oksana (Mountain School of Ukrainian Carpaty, 2022)
The article examines the role of physical education in the prevention of unsatisfactory adaptation to the learning process in a university. The purpose of the study is to identify the possibility of the discipline "Physical education" in the formation of adaptation to the educational environment of a university in students with disabilities through inclusive physical education. The research is based on the use of a complex of general scientific theoretical methods: analysis, synthesis, systematization, and generalization. It was established that inclusive physical education provides a special organization of the educational environment in a university, aimed at preventing existing negative trends in the health of students with disabilities, due to the process of adaptation, which involves technology and the organization of diagnostic and health facilities for students with disabilities. The main functions of inclusive physical education have been systematized, the implementation of which will ensure the prevention of unsatisfactory adaptation to the learning process in a university for students with disabilities: organizational and methodical, educational, correctional, educational and advisory, developmental. Among the main forms of physical improvement, it is necessary to use along with the main classes in physical education, integrated a small forms. In general, the success of the adaptation process to the educational environment for students with disabilities in the process of physical education is determined by the rational organization of methodical support aimed at strengthening the individual health of the participants in the pedagogical process, taking into account the individual characteristics of adaptation to physical loads, the step-by-step application of complex assessment methods and control. As a result, the idea of using the means of inclusive physical education as a tool for shaping the adaptation of students with disabilities to the educational environment of a university has been expanded. The latter involves the effective organization of physical education of students with disabilities for educating them in a responsible attitude to their health, and a healthy lifestyle; formation of knowledge and skills of physical culture; ensuring full-fledged physical development; physical, spiritual, and mental hardening; formation of the need for safe behavior, counteraction and prevention of negative habits, prevention of diseases; creation of conditions for active recreation in the conditions of study at a university.